Lanthanide metal-assisted synthesis of rhombic dodecahedral MNi (M = Ir and Pt) nanoframes toward efficient oxygen evolution catalysis. (December 2017) - Jin, Haneul; Hong, Yongju; Yoon, Jisun; Oh, Aram; Chaudhari, Nitin K.; Baik, Hionsuck; Joo, Sang Hoon; Lee, Kwangyeol
Abstract: Mixed metal alloy nanoframeworks have shown a great promise as electrocatalysts in water electrolyzers and fuel cells. Although a limited number of mixed metal alloy nanoframeworks have been synthesized through phase segregation of alloy phases and removal of a component, there remains a strong need for a straightforward and facile synthesis route to this important nanostructure. A wide avenue for nanoframework structures can be opened with a fail-proof method for edge-coating shape-controlled template nanoparticles. Herein, we demonstrate that lanthanide metal chlorides can selectively passivate facets of a Ni nanotemplate, leaving the edges for the growth of a secondary metal (M = Ir, Pt). The edge-deposited metal can be further in situ mixed with the underlying Ni phase to afford rhombic dodecahedral nanoframes of binary alloy phases, namely, IrNi (IrNi-RF) and PtNi (PtNi-RF). IrNi-RF showed excellent electrocatalytic activity for the oxygen evolution reaction (OER) in an acidic electrolyte, requiring and overpotential of only 313.6 mV at 10 mA cm −2 . Furthermore, even after 5000 potential cycles in the OER, IrNi-RF underwent little performance loss with an overpotential of 329.3 mV at 10 mA cm −2, demonstrating excellent catalytic stability. The presence of highly active grain boundaries, agglomeration-free frame structures, as well as the presence of IrNi/IrOx interface might be responsible for the excellent electrocatalytic activity and stability. Graphical abstract: Synthesis of MNi (M = Ir or Pt) nanoframe via facet-passivation agents and its excellent electrocatalytic activity and durability to oxygen evolution reaction in acidic electrolyte. Highlights: Facets of template Ni nanoparticle are passivated by lanthanide metal chlorides to induce selective deposition of Pt or Ir on the edges, resulting in IrNi and PtNi alloy frameworks. IrNi nanoframe exhibits a great oxygen evolution reaction (OER) performance in acidic electrolyte and retains five times higher current density than that of Ir/C after 5000 cycles at 1.53 V.